Effect of glucono delta lactone and potassium sorbate on the texture and stability of fresh goat milk cheese - Zahari, Rasmiza Z.; Ibadullah, Wan Z.W.; Rahim, Farah N.A.; Salim, Sabir; Brishti, Fatema H.; Rashid, Nor K.M.A.; Mustapha, Nor A.; Rashedi, Ismail F.M.; Abedin, Nur H.Z. (Asia-Pacific Journal of Science and Technology, 2025)
This study investigated the impact of different concentrations of Glucono Delta Lactone (GDL) and the addition of potassium sorbate on the physicochemical and microbial properties, structure, and texture of cheese during a 28-day storage period. The results showed that higher concentrations of GDL led to increased acidity in the cheese, resulting in a softer and more hydrated texture. The addition of potassium sorbate effectively controlled microbial growth, reducing Total Plate Count (TPC) and extending the cheese’s shelf life by up to 28 days. Texture analysis revealed that the samples with potassium sorbate had a better and more stable texture. GDL had concentration-dependent effects on cheese’s adhesiveness, resilience, hardness, and cohesiveness. Fourier Transformed-Infra Red (FT-IR) analysis revealed shifts in the O-H, C-H, and C=O peaks, indicating that GDL caused changes in the cheese’s chemical structure through acidification, while potassium sorbate contributed to stabilization by interacting with proteins and lipids. The combined analysis of yield percentages, moisture content, and color provides valuable insights for optimizing cheese production.